2022
DOI: 10.3389/fmed.2022.1018516
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic model for serious COVID-19 infection among older adults in Shanghai during the Omicron wave

Abstract: BackgroundThe Omicron variant is characterized by striking infectivity and antibody evasion. The analysis of Omicron variant BA.2 infection risk factors is limited among geriatric individuals and understanding these risk factors would promote improvement in the public health system and reduction in mortality. Therefore, our research investigated BA.2 infection risk factors for discriminating severe/critical from mild/moderate geriatric patients.MethodsBaseline characteristics of enrolled geriatric patients (ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Even patients with lower prehospital NEWS2 may experience exacerbation if combined with other risk factors. Compared with predictive models and markers composed of laboratory results [ 4 , 5 , 39 ], NEWS2 can be obtained by measuring physiological parameters without blood or bronchoalveolar lavage test and can be used in risk stratification to predict serious patients quickly and cheaply. This study also suggested that NEWS2 has positive correlations with prehospital care workload and consumption of medical human resources, and it is an important independent predictor for severe/critical categories of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even patients with lower prehospital NEWS2 may experience exacerbation if combined with other risk factors. Compared with predictive models and markers composed of laboratory results [ 4 , 5 , 39 ], NEWS2 can be obtained by measuring physiological parameters without blood or bronchoalveolar lavage test and can be used in risk stratification to predict serious patients quickly and cheaply. This study also suggested that NEWS2 has positive correlations with prehospital care workload and consumption of medical human resources, and it is an important independent predictor for severe/critical categories of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic model composed of white blood cells, CD4 positive T cells, and D-dimer can effectively discriminate the severe/critical state from the mild/moderate state in COVID-19 caused by SARS-CoV-2 Omicron variant BA.2 infection. This model shows a C-statistic of 0.962, a sensitivity of 97.14%, and a specificity of 90.27% [ 5 ]. However, such diagnostic models and biomarkers must be obtained by laboratory testing, which are inconvenient, time consuming, and uneconomical.…”
Section: Introductionmentioning
confidence: 99%
“…1.5 may further undermine the efficacy of the current COVID-19 vaccine and lead to a surge in breakthrough infections and re-infections. At the same time, on October 14, 2022, studies suggested that age over 80, suffering from a variety of underlying diseases, the use of immunosuppressants, chronic kidney disease, and other factors are the risk factors for developing severe disease after novel coronavirus infection, so these people need additional vaccination ( Agrawal et al., 2022 ; Bao et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the current environment where most countries cancel normalized nucleic acid testing, it is of great significance for clinicians to understand the identification of the above two diseases. Besides, most of the previous studies focused on elderly patients [12,13] , and the difference between Omicron and H1N1 influenza in young patients is rarely reported. Although young patients are often mild [14] , they should also be noticed.…”
Section: Introductionmentioning
confidence: 99%